Complex Fetal Ovarian Cysts Cause Problems Even After Regression - Karakuş, Osman Z.; Ateş, Oğuz; Hakgüder, Gülce; Olguner, Mustafa; Akgür, Feza M. (European Journal of Pediatric Surgery, 2014)
Purpose Fetal ovarian cysts' size and nature are considered as the most important factors for determining the treatment modality. When to perform an intervention and to which fetal ovarian cysts has not been clarified yet. We herein present our experience with fetal ovarian cysts.Materials and Methods The hospital records of 38 ovarian cysts (27 simple and 11 complex) were evaluated retrospectively. The prenatal and postnatal outcomes of the cysts were investigated.Results Prenatally at the 37 fetuses, 38 fetal ovarian cysts were evaluated retrospectively. There were 27 simple and 11 complex fetal ovarian cysts followed by prenatally and postnatally. None of the simple fetal ovarian cysts underwent in utero torsion. Postnatally, 23 simple ovarian cysts were regressed within 3 months. Four patients with simple ovarian cysts larger than 4 cm were operated. During follow-up period, seven complex ovarian cysts regressed, one complex ovarian cyst complicated with intestinal obstruction underwent surgery, and three complex ovarian cysts did not regress and they were operated. Three out of seven complex ovarian cysts that were initially regressed presented with intestinal obstruction and oophorectomy plus adhesiolysis were performed. Surgical treatment was required in 7 out of 11 (64%) complex ovarian cysts.Conclusion Complex ovarian cysts lead to problems even after regression in the postnatal period and require operative intervention sooner or later.
Keywords: fetal ovarian cyst; complex ovarian cyst; complicated ovarian cyst; intestinal obstruction